EU-Rotate_N – a Decision Support System – to Predict Environmental and Economic Consequences of the Management of Nitrogen Fertiliser in Crop Rotations - Rahn, C. R.; Zhang, K; Ramos, Carlos; Doltra, Jordi; De-Paz, José M.; Riley, H.; Fink, M.; Nendel, C.; Thorup-Kristensen, K.; Pedersen, A.; Piro, F.; Venezia, A.; et al. (International Society for Horticultural Science, 2020)
A model has been developed which assesses the economic and environmental performance of crop rotations, in both conventional and organic cropping, for over 70 arable and horticultural crops, and a wide range of growing conditions in Europe. The model, though originally based on the N_ABLE model, has been completely rewritten and contains new routines to simulate root development, the mineralisation and release of nitrogen (N) from soil organic matter and crop residues, and water dynamics in soil. New routines have been added to estimate the effects of sub-optimal rates of N and spacing on the marketable outputs and gross margins. The model provides a mechanism for generating scenarios to represent a range of differing crop and fertiliser management strategies which can be used to evaluate their effects on yield, gross margin and losses of nitrogen through leaching. Such testing has revealed that nitrogen management can be improved and that there is potential to increase gross margins whilst reducing nitrogen losses.